Workshop Scientific Writing Innovation (Sci-Fi) Dalam Peningkatan Kompetensi Penulisan Skripsi Mahasiswa FISIP Universitas Halu Oleo - Sarinah .; Muh. Rijal; La Ode Agus Said; Muhammad Ilham Nur Ikhsan Rintaka; Rasmin . (CV. ITTC INDONESIA, 2025)
Difficulties in writing a thesis are a common challenge faced by students at the Faculty of Social and Political Sciences, Halu Oleo University. Many students encounter obstacles in understanding the structure of scientific writing, formulating research problems, and applying appropriate research methods. To address these issues, a community service activity in the form of a Scientific Writing Innovation (Sci-Fi) Workshop was conducted as an effort to enhance thesis writing competencies. This activity aims to equip students with systematic thesis writing techniques and strategies through a participatory and innovative approach. The implementation methods include workshops, writing practicums, thesis reviews, project-based learning, and coaching clinics. The program involved 55 final-year students as participants. Evaluation results showed that approximately 85% of participants successfully drafted their theses up to Chapter III with proper structure and academic standards. Additionally, based on a satisfaction survey, over 90% of participants stated that the activity was highly beneficial and expressed hope for its regular implementation. Overall, the Sci-Fi workshop proved effective in enhancing students' scientific writing skills and building their confidence in the thesis writing process.